(3CMGOjK eNJGQI ef GdJQZjH hGdJQgjH ddCUHgGfjs - (3eLghds
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg hSdGe Ydi YHGOg GdPjf GUWai CNQL GdCUHgGfj aj GdJQZjH Yf eYGP Hf LHd bGd (B: (3bGd QShd Gddg Udi Gddg Ydjg hSde ef CMjG GddjGdj GdNeS hLHJ dg GdLfI (B: (3djdI GdJQhjI hdjdI YQaI hdjdI GdfMQ hdjdI GdaWQ hdjdI GdfUa ef TYHGfs
(3BNQgG (B:s
(3Yf CHj cQOhS Yf CHjg bGd (B: (3bGd QShd Gddg Udi Gddg Ydjg hSde ef CMjG djdI GdYjO hdjdI GdfUa ef TYHGf de jeJ bdHg jhe JehJ GdbdhH , GfJgi bGd aj GdCUd Gdefbhd efg BNQ eG hLOJ HNW eDdag QMeg Gddg JYGdis
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdMOjK hGdeUWdMs